1994
DOI: 10.1095/biolreprod51.4.655
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenesis in the Preovulatory Porcine Follicle1

Abstract: The expression of four major steroidogenic enzymes in porcine theca and granulosa cell layers of preovulatory follicles was related to the levels of steroids in follicular fluid and gonadotropin concentrations in peripheral serum at slaughter. Ovaries were collected during proestrus, early estrus, and late estrus as evidenced by behavioral signs. Follicles were dissected from the ovaries, and theca, granulosa, and follicular fluids were pooled for each of 24 sows. Cytochromes P450 17 alpha-hydroxylase/17-20 ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 21 publications
11
57
1
Order By: Relevance
“…Follicular fluid progesterone and estradiol-17β concentrations, and progesterone/estradiol-17β ratios in healthy and atretic follicles of pigs are summarized in Table 2. The ranges of concentrations of estradiol-17β (1.5 to 23 ng/ml), and progesterone (116 to 335 ng/ml) in follicular fluid correspond well with previously reported values [12,17,18]. Follicular fluid progesterone concentration was 2.21-fold higher (P<0.001) in atretic than in healthy follicles.…”
Section: Figsupporting
confidence: 89%
See 3 more Smart Citations
“…Follicular fluid progesterone and estradiol-17β concentrations, and progesterone/estradiol-17β ratios in healthy and atretic follicles of pigs are summarized in Table 2. The ranges of concentrations of estradiol-17β (1.5 to 23 ng/ml), and progesterone (116 to 335 ng/ml) in follicular fluid correspond well with previously reported values [12,17,18]. Follicular fluid progesterone concentration was 2.21-fold higher (P<0.001) in atretic than in healthy follicles.…”
Section: Figsupporting
confidence: 89%
“…In pigs, estradiol-17β production by atretic follicles is decreased, but production of progesterone is increased [18]. Thus, the progesterone/estradiol-17β ratio of follicular fluid in each follicle provides a good index of follicular atresia in pig ovaries [17,18]. The present study showed that there is a high correlation (r=0.892) between the Ca 2+ /Mg 2+ -dependent endonuclease activity of granulosa cell nuclei prepared from atretic follicles and the progesterone/estradiol-17β ratio of the follicular fluid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the cytochrome P450 11A (CYP11A) and the STAR protein (STAR) genes, not present on our micro-arrays and whose expression was already known to increase during the terminal development of the follicle (Hatey et al 1992, Conley et al 1994 gave the expected results. GSTA1 gene expression, first ranked (score 222) with the RF analysis as a predictive marker for follicle size class with a relatively high expression fold change (2.58) between LF and SF, was examined by in situ hybridization (Fig.…”
Section: Differential Expression Validation By Quantitative Real-timementioning
confidence: 76%